FACTORS INFLUENCING POTATO FARMER’S SATISFACTION WITH THE QUALITY OF AGRICULTURAL EXTENSION SERVICES IN PLATEAU STATE, NIGERIA - Bedima, C. G.; Garba, M.; Abdullahi, S. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The study examined the factors influencing potato farmers’ satisfaction with quality of agricultural extension services in Plateau State, Nigeria. Multi-stage sampling technique was employed in selecting 209 farmers. Data were collected through the administration of structured questionnaires and analyzed using both descriptive and inferential statistics. The results showed that majority (63.4%, 79.7% and 64.9%) of the Irish potato farmers were male, married and had attended tertiary levels of education respectively. The results also reveal that majority (70.8%, 67.8% and 67.3%) of the Irish potato farmers had a farm size of 0.5-2.6ha, 110 persons per household and were within the age bracket of 32-45 years respectively. The result also shows that Irish potato farmers were highly satisfied with method of farmers training (2.7), provision of inputs (2.7) and relevance of innovation to farmers (3.1). On the other hand, the result also shows that sex (r= 6.680), marital status (r= 6.513) and membership of association (r= 7.055) were significant (P<0.01) in influencing Irish potato farmers satisfaction with extension service delivery . The study further reveals that inadequate training to farmers (93.6%), financial constraints (88.6%) and poor farmers outreach (68.8%) were the major constraints to Irish potato farmers satisfaction with extension services delivery. The study concludes that sex, marital status and membership of associations were the factors influencing Irish potato farmers satisfaction with extension service delivery. The study recommends that irish potato farmers should form and actively participate in farmers’ cooperatives/association to increase their access to extension services and credit, government should assist irish potato farmers by providing inputs at subsidized rates.